Prognostic significance of body mass index and weight loss in patients with idiopathic pleuroparenchymal fibroelastosis - Kono, Masato; Saito, Takahiko; Tsunoda, Tomo; Ikeda, Shin; Arano, Takahiro; Watanuki , Masayuki; Katsumata, Mineo; Miwa, Hideki; Miki, Yoshihiro; Hashimoto, Dai; Suda, Takafumi; Nakamura, Hidenori (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Idiopathic pleuroparenchymal fibroelastosis (IPPFE) is a rare form of idiopathic interstitial pneumonias; its physical characteristics include a slender build with platythorax and progressive weight loss. However, the clinical significance of body mass index (BMI) and weight loss remains unclear in patients with IPPFE. Therefore, we aimed to clarify the association between baseline BMI, weight loss after diagnosis, and the prognosis of patients with IPPFE. Methods: This retrospective study included 71 patients diagnosed with IPPFE at our institution between 2005–2021. BMI at diagnosis was classified into three: underweight (<18.5 kg/m2), normal weight (≥18.5 to <25.0 kg/m2), or overweight (≥25.0 kg/m2). An annual rate of weight change after the diagnosis was evaluated, and ≥5% per year decrease was defined as a significant weight loss. We investigated clinical features and prognosis based on baseline BMI and weight loss. Results: Of the 71 patients, 48 (67.6%) and 23 (32.4%) were classified as underweight and normal weight, respectively, and none were overweight. Significant weight loss occurred in 24 (33.8%) patients, and they tended to have more cases of dyspnea and had significantly older age, lower BMI, higher rates of co-existence of lower-lobe interstitial lung disease, lower pulmonary function test results and higher incidence of pneumothorax after the diagnosis than those without weight loss. Patients with BMI <18.5 kg/m2 and those with weight loss had a significantly worse prognosis than those with BMI ≥18.5 kg/m2 or those without weight loss, respectively (p=0.005, p<0.001). Multivariate analysis revealed that low BMI and weight loss were independent poor prognostic factors. Conclusions: Low BMI and weight loss are associated with poor prognosis in patients with IPPFE.